Prominent Optic Disc Featured in Inherited Retinopathy - Todorova, M. G.; Bojinova, R. I.; Valmaggia, C.; Schorderet, D. F. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background We investigated the relationship between prominent optic disc (POD) and inherited retinal dystrophy (IRD). Patients and Methods A cross-sectional consecutive study was performed in 10 children and 11 adults of 7 non-related families. We performed clinical phenotyping, including a detailed examination, fundus autofluorescence, and colour fundus and OCT imaging. Genetic testing was subsequently performed for all family members presenting retinal pathology. Results In 4 members of a 3-generation family, hyperfluorescent deposits on the surface of POD were related to a p.(L224M) heterozygous mutation in BEST1. In the second family, one member presented deposits located on the surface on hyperaemic OD and a compound p.(R141H);(A195V) mutation in BEST1. In the third family, POD was observed in father and child with early onset cone-rod dystrophy and a novel autosomal recessive p.(W31*) homozygous mutation in ABCA4. In the fourth family, POD with “mulberry-like” deposits and attenuated vessels were observed in a 7-year old girl, with a mutation in USH1A, and with early onset rod-cone dystrophy, associated with hearing loss. In the fifth family, blurry OD with tortuous vessels was observed in 4 consanguineous female carriers and a hemizygous boy with a p.(R200H) mutation in the X-linked retinoschisis RS1. In the sixth family, a mother and her son were both affected with POD and attenuated peripapillary vessels, and presented with a p.(Y836C) heterozygous mutation in TOPORS, thus confirming autosomal dominant RP. In the seventh family, in 3 family members with POD, compound p.(L541P;A1038 V);(G1961E) mutations in ABCA4 confirmed the diagnosis of Stargardt disease. Conclusions A variety of OD findings are found in a genetically heterogeneous group of IRDs. In the presence of POD, an inherited progressive photoreceptor disease should be ruled out.
Keywords: prominent optic disc; inherited retinopathy; mutation